Diana, the Challenger: A Feminist Figure of Power and Salvation in Hollywood Feminist Fantasy Wonder Woman (2017) - Fayaz Khan (University of Chitral Journal of Linguistics and Literature, 2023)
Jenkins (2017) Wonder Woman is a portrayal of traditional role of feminism, in which masculine traits including courage, strength, leadership, independence and assertiveness are used to overwhelm male-dominant society, while manhood as a masculine trait is challenged by a woman constantly striving for power and authority. Marriage is shown as a failed philosophy in the movie, while men are shown just a minimal need to procreate. ‘Wonder Woman’ has an extensive gay male and lesbian fan base. This task approaches Wonder Woman with a semiotic and cultural examination to perceive how her character is comprised of some syntagmas that empower this sort of identification like same-sex society, battling bigotry, discovering one's place, and flourishing in transformation. The analysis shows that the virtue of fighting for peace in Diana has been compromised with the amalgamation of feminists’ radical approach. She has been presented as a female rebellion, while the rightful cause of the care-taker feminists has been degenerated by the amalgamating of bad feminism with good feminism.